PENGARUH SUBSTITUSI GONDORUKEM PADA ASPAL PENETRASI 60/70 DENGAN MENGGUNAKAN AGREGAT HALUS SABANG TERHADAP STABILITAS MARSHALL - Cut Nawalul Azka; Sofyan M. Saleh; Sugiarto Sugiarto (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Basically, aggregate is the one of pavement capacity. The determining of fine aggregate Sabang has low quality because the value absorption is 4.45% greater than 3%. The purpose of this research is to identify the effect of gum rosin substitution on asphalt penetration 60/70 with fine aggregate sabang for Marshall characteristics.The trial method is Marshall method by using dry process. Based on the research results the value of optimum bitumen is 5.87%. from the research result it can be concluded that if the greater value of aggregate then the weight from those type of aggregate is smaller so the weight of the type of maximum mixture become small, whereas the smaller value of aggregate porosity then the weight of the type from those aggregate is larger so that the weight of the maximum type mixture became much larger. The percentage aggregate variation (AHS 50%:AHI 50%), (AHS 75%:AHI 25%), and (AHS 100%:AHI 0%). The results showed the value stability is lower, when percentage of fine aggregate sabang  more excessively. The best value stability is 50% of fine aggregate sabang and 50% and aggregate from Aceh Besar. The utilizing of value percent fine aggregate sabang that excess is poor in quality, because binding strength not efectif. One way anova show the value of  density, VIM, VMA, VFA, Stability Flow and Marshall shows is F count is larger than the value F table and the value of sig. smaller than the value of  , it’s means Ho is rejected and Ha is accepted, meaning is influential.